Unveiling the thermometric sensitivity of Eu3+ doped glasses in various system from theory to experimental. (1st April 2023) - Bondzior, Bartosz; Hoang, Thu; Vu, T.H. Quan; Dereń, Przemysław J.; Petit, Laeticia
Abstract: The thermometric sensitivity of the glasses in different Eu 3+ doped glasses in different glass systems with different phonon energies and structures was obtained theoretically using the Judd-Ofelt parameters and compared to the experimental data obtained from the temperature dependent emission spectra. The purpose of the study was to test the limits of thermal sensitivity estimation from the Judd-Ofelt parameters in a wide selection of glass systems. We show, for the first time, the discrepancies in the theoretical and experimental values for the germanate and tellurite glasses due to their low phonon energies which cause the Boltzmann model to fail. The phosphate glasses, due to their high absolute thermometric sensitivity, are the promising materials as luminescence thermometer. Graphical abstract: Image, graphical abstract